PENGARUH FUNGI MIKORIZA ARBUSKULA DAN UREA TERHADAP PERTUMBUHAN BIBIT LADA - NURMI KURNIATI; IWAN SASLI; DWI ZULFITA (Jurnal Sains Pertanian Equator, 2017)
PENGARUH FUNGI MIKORIZA ARBUSKULA DAN UREA TERHADAP PERTUMBUHAN BIBIT LADA Nurmi Kurniati (1), Iwan Sasli (2), Dwi Zulfita (2) (1)   Mahasiswa Fakultas Pertanian (2)   Dosen Fakultas Pertanian Universitas Tanjungpura, Pontianak ABSTRACT Effort for get healthy and qualified black pepper seedling can we do with usage of Arbuscular Mycorrhizal Fungi (AMF) and urea fertilization. This research aims to knows interaction between AMF inoculation and urea fertilization to black pepper seedling growth, know influence of AMF inoculation and urea fertilization to black pepper seedling growth, finds the best dosage of urea to black pepper seedling growth. This research was carried out at sungai guntung subvillage, sungai palah village, galing district, sambas regency. The time of research was on going from may,  2016 untill august,  2016. The method was used Completely Randomized Design (CRD) with factorial. The first factor is AMF (M) and the second factor is urea (U). The threatment are used AMF consist of two levels,  : without FMA,  : AMF and Urea,  : without urea,  : 2,5 g urea, ,  : 5 g urea,  : 10 g urea. Observed variables in this study were, number of leaves (pieces), plant dry weight (g), root infection by mycorrhizae (%), leaf area ( ), leaf chlorophyll content (SPAD units), and P uptake (g). The result showed with FMA inoculation able to increase black pepper seedling growth. Urea fertilization with various of dosage able to increase black pepper seedling growth. The interaction between AMF and urea don’t increase black pepper seedling growth.   Keyword: Black Pepper, Growth, Mycorrhiza Fungi, Urea